Fabrication of Al–Cu laminated composites by diffusion rolling procedure. (August 2014) - Yang, Y. H.; Lin, G. Y.; Chen, D. D.; Zhang, R.; Wang, D. Z.; Qi, F.
<x content-type="archive" xml:space="preserve">Abstract</x> A diffusion rolling procedure was employed for the fabrication of Al–Cu laminated composites; the microstructure and mechanical properties of the interface were investigated. With diffusion bonding initially, intermetallic compounds (IMCs) occurred at the Al/Cu interface. After plastic deformation by rolling the laminated composites, the interface strip of IMCs broke and became discontinuous equiaxed particulates. Compared with roll bonding with heat treatment and diffusion bonding, the shear tensile strength of two-stage processed Al/Cu interface reached a maximum value equivalent to 90% of that of Al. Therefore, it is concluded that the diffusion rolling procedure yielded the highest strength of Al–Cu laminated composites.